Metabolic Engineering of Bacillus subtilis Toward Taxadiene Biosynthesis as the First Committed Step for Taxol Production - Abdallah, Ingy I.; Pramastya, Hegar; van Merkerk, Ronald; Sukrasno,; Quax, Wim J. (Frontiers in Microbiology, 2019)
Terpenoids are natural products known for their medicinal and commercial applications. Metabolic engineering of microbial hosts for the production of such valuable compounds, as artemisinin and Taxol, has gained vast interest in the last few decades. The Generally Regarded As Safe (GRAS) Bacillus subtilis with its broad metabolic potential is considered one of these interesting microbial hosts. In the effort toward engineering B. subtilis as a cell factory for the production of the chemotherapeutic Taxol, we expressed the plant-derived taxadiene synthase (TXS) enzyme. TXS is responsible for the conversion of the precursor geranylgeranyl pyrophosphate (GGPP) to taxa-4,11-diene, which is the first committed intermediate in Taxol biosynthesis. Furthermore, overexpression of eight enzymes in the biosynthesis pathway was performed to increase the flux of the GGPP precursor. This was achieved by creating a synthetic operon harboring the B. subtilis genes encoding the 2-C-methyl-D-erythritol-4-phosphate (MEP) pathway [dxs, ispD, ispF, ispH, ispC, ispE, ispG] together with ispA (encoding geranyl and farnesyl pyrophosphate synthases) responsible for providing farnesyl pyrophosphate (FPP). In addition, a vector harboring the crtE gene (encoding geranylgeranyl pyrophosphate synthase of Pantoea ananatis) to increase the supply of GGPP was introduced. The overexpression of the MEP pathway enzymes along with IspA and GGPPS caused an 83-fold increase in the amount of taxadiene produced compared to the strain only expressing TXS and relying on the innate pathway of B. subtilis. The total amount of taxadiene produced by that strain was 17.8 mg/L. This is the first account of the successful expression of taxadiene synthase in B. subtilis. We determined that expression of GGPPS through the crtE gene is essential for formation of sufficient precursor GGPP in B. subtilis as its innate metabolism is not efficient in producing it. Finally, the extracellular localization of taxadiene production by overexpressing the complete MEP pathway along with IspA and GGPPS presents the prospect for further engineering aiming for semi-synthesis of Taxol.